2009
DOI: 10.1080/01421590802530898
|View full text |Cite
|
Sign up to set email alerts
|

A ten-year review of the literature on the use of standardized patients in teaching and learning: 1996–2005

Abstract: Most studies reported that the educational use of SPs was valuable. More rigorous studies would support the evidence-based use of SPs in teaching and learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
155
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(161 citation statements)
references
References 67 publications
3
155
0
3
Order By: Relevance
“…In a review of communication skills training (Aspegren 1999), experiential methods were reported to be more effective in teaching communication skills than instructional methods. Nowadays experiential methods such as SPs and RP are widely used in communication skills training (Lane & Rollnick 2007;Cleland et al 2009;May et al 2009;Hargie et al 2010). SPs portray live interactive simulations of specific communication challenges and medical problems, offering the students a safe learning environment with no risk of harm to real patients (Kurtz et al 2005).…”
Section: )mentioning
confidence: 99%
“…In a review of communication skills training (Aspegren 1999), experiential methods were reported to be more effective in teaching communication skills than instructional methods. Nowadays experiential methods such as SPs and RP are widely used in communication skills training (Lane & Rollnick 2007;Cleland et al 2009;May et al 2009;Hargie et al 2010). SPs portray live interactive simulations of specific communication challenges and medical problems, offering the students a safe learning environment with no risk of harm to real patients (Kurtz et al 2005).…”
Section: )mentioning
confidence: 99%
“…Standardized clients are individuals paid to learn and simulate a pre-established clinical scenario in the field of health education. [16,17] In this study, each of the standardized clients simulated a specific clinical scenario and were asked to repeat and maintain the same performance with each participant (eight non-OTs with different job titles using Algo), without considering the previous participant's performance. The chosen standardized clients had consistent social history, physical characteristics and home environment with his/her simulated clinical scenario.…”
Section: Simulated Clinical Scenariosmentioning
confidence: 99%
“…To estimate interrater reliability, non-OTs with different job titles administered Algo to six standardized clients, [16,17] and their recommendations were compared.…”
Section: Designmentioning
confidence: 99%
“…18 The use of standardized patients, actors, or actual patients trained to portray a patient and score student performance on a rating scale is evidenced to be an effective means of teaching communication skills across various healthcare professions. 19,20 This method has been widely used in both medical and pharmacy education. 1,18,21 Recognizing the importance of motivational interviewing in pharmacy education, the primary objective of this study is to evaluate and compare the impact of learning and assessment methods on student attainment of motivational interviewing skills.…”
Section: Introductionmentioning
confidence: 99%